Management turbulence at ACR Retakaful Berhad - Khairat, Delil; Hassan, Arif (Graduate School of Management, International Islamic University Malaysia, 2013)
This case discusses the issues that arose during the change process in a Kuala Lumpur based Retakaful company, ACR Retakaful Berhad. The chain of catastrophic events in Asia during the years 2010 and 2011 had raised a huge number of claims against the company which went into financial difficulties. The company had no option but to change. A new CEO arrived and quickly took serious measures to rectify the situation and put the company on the right track in order to secure sustainability, growth and profitability. However, the change process was not running smoothly. Employees were not involved in the change and many chose to withdraw voluntarily. Subsequently, staff turnover reached the highest level ever known in its history. Instead of moving to a better state, the company’s performance was getting worse with each passing day.